Optimization of Mahakam Sand and Lightweight Brick Waste Utilization as Fine Aggregates in the Production of Class D Paving blocks - Fazriyan, Helmi; Liana, Ulwiyah Wahdah Mufassirin; Pitoyo, Pitoyo (Jurnal Teknik Sipil, 2025)
. In the increase in construction projects using lightweight bricks, the amount of waste generated has also increased. To address this issue, this research evaluates the use of lightweight brick waste as a replacement for Mahakam sand in the production of paving blocks according to SNI 03-0691-1996. The experimental method was used with control test objects without lightweight brick waste and test objects with varying amounts of lightweight brick waste. The mixture composition was 1pc:6ps with a water-cement ratio of 0,35, and lightweight brick waste constituting 0%, 25%, 50%, 75%, and 100% of the sand weight. The Paving blocks were made using manual compaction tools. Compressive strength testing was conducted at 3, 7, and 28 days, while absorption testing was done by soaking for 1 day. The results showed that paving blocks with 50% lightweight brick waste had the highest compressive strength at 28 days, reaching 47,81 MPa, classified as class A. The addition of lightweight brick waste also increased the water absorption of the Paving blocks, with the lowest absorption in the 25% mixture at 2,17%, also classified as class A. These findings demonstrate the potential for using lightweight brick waste in the production of environmentally friendly paving blocks.